Cytopathological Analysis of Fine Needle Aspiration of Breast Lumps at a Tertiary Level Hospital in Nepal - Bhandari, Anita; Baral, Alina; Sharma, Sharad (Journal of Bharatpur Hospital, 2026)
BackgroundBreast lumps constitute a significant proportion of pathological conditions encountered in clinical practice, ranging from benign lesions to malignant neoplasms. Fine-needle aspiration cytology (FNAC) serves as an established method for the cytological assessment of breast lumps. This study is aimed at evaluating cytopathological spectrum of breast lesions utilizing FNAC at a tertiary-level hospital in Nepal.MethodsA cross-sectional observational study was conducted including 105 patients who underwent FNAC for breast lumps between 1st October 2023 till 30th September 2024 at Bharatpur Hospital. FNAC was performed under aseptic conditions, with aspirated material smeared on glass slides and stained using Papanicolaou and May-Grünwald-Giemsa techniques. Cytological findings were recorded in the departmental register, and relevant demographic data were extracted. ResultsThe mean age of participants was 37.6 ± 14.4 years with 89% females and 11% males. Lesions were observed in the left breast in 51.4% of cases, the right breast in 44.8%, and bilaterally in 3.8% of patients. Fibroadenoma was the most common lesion observed in 53.3%, while gynecomastia occurred exclusively in 11.4% males. Malignant and suspicious lesions accounted for 15.2% of cases. Other benign lesions included 6.7% breast abscess, 3.8% galactocele, 2.9% fibrocystic changes, and rare entities such as granulomatous mastitis, duct ectasia, and lipoma. ConclusionsThe cytopathological spectrum of breast lesions was dominated by benign lesions, with fibroadenoma being the most frequent cytological diagnosis. Malignant lesions accounted for a smaller proportion of cases. These findings enhance the existing evidence on the cytopathological spectrum of breast lesions in Nepal.